Mass spectra analysis of neon, chlorine, argon, and krypton - Aston, Francis William (Isotopes, 1922)
Mass spectra illustration depicts an analysis of elements including neon, chlorine, argon, and krypton. Digitized in entirety, this work on isotopes covers topics including radioactive isotopes, positive rays, neon, the mass spectrograph, analysis of the elements, electrical theory of matter, atomic numbers, spectra and analysis of elements. Illustrations throughout text including four plates.
Keywords: Spectrum analysis; Isotopes; Neon; Mass spectrometry; Radioactivity